Do Ethics Matter? Tax Compliance and Morality - Alm, James 1950-; Torgler, Benno 1972- (2011)
In this article we argue that puzzle of tax compliance can be explained, at least in part, by recognizing the typically neglected role of ethics in individual behavior; that is, individuals do not always behave as the selfish, rational, self-interested individuals portrayed in the standard neoclassical paradigm, but rather are often motivated by many other factors that have as their main foundation some aspects of “ethics.” We argue that it is not possible to understand fully an individual’s compliance decisions without considering in some form these ethical dimensions. Specifically, we argue here that there is much direct and indirect evidence that ethics differ across individuals and that these differences matter in significant ways for their compliance decisions. We then put this in the larger context of the inability of the standard neoclassical paradigm to explain compliance of at least some individuals, and we suggest several possible avenues by which theory can be expanded to incorporate ethics. We conclude by arguing that a full house of compliance strategies is needed to combat tax evasion, strategies that include the traditional “enforcement” paradigm suggested by and consistent with neoclassical theory, a less traditional “service” paradigm that recognizes the important role of a “kinder and gentler” tax administration in encouraging compliance, and, importantly, a new “trust” paradigm that is built on the foundation of ethics, in which the tax administration must recognize that it can erode the ethics of taxpayers by its own decisions.
Keywords: Tax evasion; expected utility theory; Ethics; economics-of-crime